TOXICITY STUDY OF ARSENIC AND NICKEL IN POTENTIAL FUNGI IN MYCOREMEDIATION - Chin, Hui Rong (2018)
Pollution is getting more and more severe due to the anthropogenic discharge of harmful chemical such as heavy metal contamination such as arsenic, nickel. When the concentration of heavy metals are too high, they will bring harmful effects to those living organisms that are exposed for a long duration of time like plants, animals and human health. Bioremediation such as mycoremediation is a preferable method to remove these pollutants because it is cheap, environmental friendly and it is most likely to completely degrade pollutant. The objective of this research study is to identify the potential fungi in remediating nickel (Ni) and arsenic (As) pollution based on their tolerance level to the heavy metal. Therefore, different concentration of As and Ni is used to test the tolerance level of the fungal and each fungal have three replicate. The potential fungi that were tested to remediate As and Ni are Trichoderma longibrachiatum, Hypocrea koningii, Penicllium simplicissimum, Penicillium chrysogenum and Aspergillus ustus. The total growth of fungi was determined based on their dry weight (g/weeks). One way analysis of variance (ANOVA) with PostHoc tests (LSD and Dunnett T3) in SPSS software were used to analyse the growth rate of fungi. The highest tolerance to As and Ni was Aspergillus ustus (up to 20ppm with biomass of 0.09 g/weeks).The lowest tolerance to As and Ni was Trichoderma longibrachiatum (up to 20ppm with biomass of 0.03 g/weeks).